The Developed Method for Evaluation of the Oil Spot of Engine Oil of Motor Vehicles by Comprehensive Criteria for Diagnostics of the Technical Condition of Engine Oil (Texas Journal of Engineering and Technology, 2022)
A technique has been developed for correcting the frequency of maintenance of an internal combustion engine of motor vehicles according to a complex criterion for diagnosing the technical condition of engine oil. The dependence of the frequency of oil change of motor vehicle engines on the developed complex criterion was determined